2011
DOI: 10.1200/jco.2011.37.9453
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Secretion After Conformal Radiation Therapy in Pediatric Patients With Localized Brain Tumors

Abstract: A B S T R A C T PurposeGrowth hormone deficiency (GHD) after radiation therapy negatively affects growth and development and quality of life in children with brain tumors. Between 1997 and 2008, 192 pediatric patients with localized primary brain tumors (ependymoma, n ϭ 88; low-grade glioma, n ϭ 51; craniopharyngioma, n ϭ 28; high-grade glioma, n ϭ 23; and other tumor types, n ϭ 2) underwent provocative testing of GH secretion by using the secretogogues arginine and L-dopa before and after (6, 12, 36, and 60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
80
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(85 citation statements)
references
References 21 publications
4
80
0
1
Order By: Relevance
“…453 A few studies have considered the incidence and importance of cardiac arrhythmias long after chemotherapy by guest on http://circ.ahajournals.org/ Downloaded from during childhood. Although some have reported occasional instances of sudden death 177 that may be related to repolarization abnormalities (QT prolongation and abnormal QT dispersion) in association with ventricular dysfunction, 455 others have described only infrequent and clinically unimportant arrhythmias. 456 Other studies of pediatric cancer survivors have described ventricular arrhythmias in association with late ventricular dysfunction, 457 but in general, these studies have been small and were not systematic evaluations of the population at risk.…”
Section: Screening For Arrhythmias and Conduction Defectsmentioning
confidence: 99%
See 1 more Smart Citation
“…453 A few studies have considered the incidence and importance of cardiac arrhythmias long after chemotherapy by guest on http://circ.ahajournals.org/ Downloaded from during childhood. Although some have reported occasional instances of sudden death 177 that may be related to repolarization abnormalities (QT prolongation and abnormal QT dispersion) in association with ventricular dysfunction, 455 others have described only infrequent and clinically unimportant arrhythmias. 456 Other studies of pediatric cancer survivors have described ventricular arrhythmias in association with late ventricular dysfunction, 457 but in general, these studies have been small and were not systematic evaluations of the population at risk.…”
Section: Screening For Arrhythmias and Conduction Defectsmentioning
confidence: 99%
“…175 Radiation to the neck can damage the carotid arteries, increasing the risk of stroke, even without hormonal changes, as discussed further under the sections below entitled "Treatment of Radiation-Associated CVD Risk Factors" and "Cardiometabolic Risk Factors for Premature Atherosclerosis." 29,176,177 In addition, spinal radiation used to treat brain malignancies may include the heart in the treatment field. Jakacki et al 178 reported in 1993 that subclinical cardiac dysfunction and conduction abnormalities were greater in survivors who received such therapy than in those who received flank radiation, in which the heart was not in the treatment field.…”
mentioning
confidence: 99%
“…Radiation therapy is thought to play a role in malignant transformation of PLGG, 5 particularly in the context of cancer predisposition. 6,7 Before the genomic era, Broniscer et al 3 were the first to describe several genetic events that occur in these cancers. Recent next-generation sequencing efforts have uncovered somatic mutations in TP53, ATRX, and IDH1/2, among other alterations that are present in adult…”
Section: Introductionmentioning
confidence: 99%
“…Skeletal growth, bone health, body composition, and metabolic homeostasis may be impaired as a consequence of radiation-induced endocrine deficits or because of direct radiation-related toxicity. The effect of radiotherapy on the various endocrine organs is dictated primarily by the total dose received and the duration since treatment such that the risk increases with increasing doses and greater elapsed time between exposure and follow-up [5-7]. Additional considerations include fraction size and number [8] and the method of delivery of the radiation [9-11].…”
Section: The Effect Of Radiotherapymentioning
confidence: 99%
“…The most common childhood CNS tumors treated with radiotherapy include medulloblastoma, craniopharyngioma, ependymoma, high-grade glioma, and low-grade glioma [5, 14]. Other childhood malignancies that may require cranial radiotherapy include acute lymphoblastic leukemia (ALL), previously for prophylaxis and currently for treatment of CNS disease [15], and malignant non-brain solid tumors of the head or neck (e.g., nasopharyngeal carcinoma, retinoblastoma, and rhabdomyosarcoma) [16].…”
Section: The Effect Of Radiotherapymentioning
confidence: 99%